From Emptiness to Acceptance: the Phenomenology of Adolescent Loneliness After the Loss of a Parent - Rizky Amayana Saputri; Dwi Sona; Iin Andini Ismail; Wardah Hafizhah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Loneliness is one of the most significant psychological impacts experienced by adolescents after the loss of a parent, particularly due to the absence of an attachment figure who previously provided emotional security. This study aims to describe the subjective experience of loneliness among bereaved adolescents. Using a qualitative approach with descriptive phenomenology, three adolescents aged 13–18 participated in in-depth interviews supported by source triangulation. Data were analyzed using Giorgi’s Descriptive Phenomenological Analysis (DPA). The findings revealed four main themes: (1) profound emptiness and deep loneliness, (2) coping strategies through distraction and alternative activities, (3) personal changes and a gradual process of grief acceptance, and (4) shifts in family roles and increased responsibilities. These results indicate that adolescent loneliness is not solely caused by the physical absence of a parent but also by the loss of emotional grounding and the emergence of greater psychosocial burdens. This study contributes to expanding phenomenological understanding of loneliness in bereaved adolescents and highlights the need for adequate psychosocial support to foster healthier adaptation.